Pemanfaatan Pekarangan Rumah dengan Bercocok Tanam Melalui Metode Hidroponik - Jafaruddin, Nurhana (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2021)
The community service activity held for PKK RT 06, Jakasetia Village, South Bekasi, aims to address the issue of restricted land in urban areas, which can be an impediment to farming. Farming with hydroponic techniques is one of the efforts that can be made. This service activity intends to use residential yards as potential land, grow vegetables fit for consumption by family members, and raise awareness of good and successful hydroponic farming practices. The Participatory Action Research (PAR) method was used in this activity, which included counseling, plant training, and talks about hydroponic practices. Providing material, tutorials on how to build hydroponic plants, and discussions are all stages of service operations. The outcomes of this activity revealed that the PKK group's knowledge of how to make home yards more lovely and gorgeous without requiring too much land elicited passionate replies and even a strong desire to try making plants using hydroponic technology.